Faktor yang Berhubungan dengan Beban Keluarga dalam Merawat Aktifitas Sehari-hari pada Lansia - Rizky Erwanto (Alma Ata University Press, 2016)
Treatment of elderly needs to be considered properly, the elderly who have difficulty in performing daily activities at home, such as toileting, eating, dressing, bathing and transferring. Issues relating to the elderly lead to dependence on others. Elderly dependency ratio can be classified in decreasing independence. Elderly needs family to perform their activities of daily living independently. Caring for the Elderly may have an impact on family in the form of expenses incurred for the elderly require continuous assistance. This research aim was to identify several factors related to the family burden of caring for the elderly in the treatment daily activities. The study design used cross sectional method. The sampling method used cluster sampling technique. Respondents that family members caring for the elderly totaling 98 respondents. The study was conducted in July 2015. Bivariate test used chi-square test. Based on bivariate analysis between knowledge and family expenses 0.002. Socioeconomic relations that includes education, employment, and income with the burden of the family, education was obtained p-value 0.039, 0.017 jobs, and income 0.0. The relationship between long care for the elderly load was obtained p-value 0.024. There were a significant relationship between the knowledge of the family, economic sosial of the family and long of care for the elderly with the burden of caring for elderly relatives. Families should aim to increase knowledge about the care activities of daily living in the elderly with a lot of reading and find out about the care activities of daily living in the elderly through mass media. Cadres should increase the knowledge about the knowledge of the care activities of daily living by means of training and counseling held in the clinic so in practice cadres received extensive insight maintenance activities of daily living in the elderly and families teach the elderly.